Walkability Index Value Jalur Pejalan Kaki di Kawasan Heritage Sebagai Pengembangan Perdagangan dan Jasa di Jalan Tunjungan, Surabaya - Khizqilla, Favian; Hidayah, Ulul (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
Walking is one of the physical activities that uses the feet as the main tool in moving, walking activities are included in the universal cheap transportation modes that are easily found in developed cities, to connect the movement of human activities from one area to another, so that socio-economic and cultural activities are created. This walking activity is a fundamental aspect of the city, where the centers of large urban economic activities depend on one of them on walking activities. A city that is friendly to walking activities is called a city with the character of Walkable City or a city that is friendly to pedestrians and the environment, while the status of a Walkable City can be known by analyzing the Walkable City Value (WIV) or the pedestrian-friendly index value of an observed area. The Walkable City concept promotes walking activities as the main means of transportation with the aim of improving a healthier lifestyle that is more environmentally friendly. In the city of Surabaya there are many centers of economic distribution, one of which is Jalan Tunjungan, the road is included in the Heritage area which has a center of economic, social and cultural activities, so that in any case it requires an analysis of the Walkability Index Value on the pedestrian path on the road. This study aims to analyze WIV on the Tunjungan Street lane, the analysis was conducted using the actual direct participatory observation method, in the observation area using a Likert scale questionnaire that was previously compiled. The results of this study are the Walkability Index Value of the Tunjungan Street Heritage Area, which is 86 out of a maximum score of 100. This value indicates that the quality of the Tunjungan Street Heritage Area is included in the "Highly Walkable" category.